Adubação potássica e alturas de corte nos aspectos morfológicos, bromatológicos e de nutrição das forrageiras Megathyrsus maximus cv. MG-12 paredão e mombaça - Coelho, Moniky Suelen Silva (2022)
It is very important to choose a forage that is responsive to fertilization, among them is the Megathyrsus maximus. MG-12 Paredão and Mombaça were submitted to five doses of potassic fertilization and cutting heights, in an attempt to extract the maximum potential of regrowth and use of nutrients from the grasses. The experiment was conducted in a shaded house at the Federal University of Mato Grosso Campus (Cuiabá), in the period from April to December 2018, in which two experiments were conducted in randomized blocks, factorial scheme 5x3, being five doses of potassium fertilization (0; 30; 60; 90 and 120 kg of K2O /ha), three cutting heights (5; 15 and 30 cm), having 60 plots (pots) for each cultivar, the cuts in the due heights was done every 30 days. The following were evaluated Plant height, number of leaves per pot, number of tillers per pot, dry mass, CP, FDN, FDA, and the contents of macronutrients. For data analysis, the statistical program SISVAR was used, in which the data were subjected to analysis of variance and test of the mean for qualitative factors (cutting height) and regression for quantitative factors (doses of potassium). The cutting height of 30 cm in forages, promoted greater plant height and crude protein content in Megathyrsus maximus forages cultivars MG-12 Paredão and Mombaça. Recommended doses of 88.62 kg of K2O/ha (7.69% of CP) and 64.40 K2O/ha (8.21% of CP), for the grasses MG-12 Paredão and Mombaça, respectively. Doses above these levels resulted in lower crude protein, nitrogen, calcium, and magnesium contents in Paredão and Mombaça grasses.